Immunoproteasome Inhibition Impairs T and B Cell Activation by Restraining ERK Signaling and Proteostasis - Schmidt, Christian; Berger, Thilo; Groettrup, Marcus; Basler, Michael (Frontiers in Immunology, 2018)
Immunoproteasome (IP) inhibition holds potential as a novel treatment option for various immune-mediated pathologies. The IP inhibitor ONX 0914 reduced T cell cytokine secretion and Th17 polarization and showed pre-clinical efficacy in a range of autoimmune disorders, transplant-allograft rejection, virus-mediated tissue damage and colon cancer progression. However, the molecular basis of these effects remained largely elusive. Here, we analyzed the effects of ONX 0914 in primary human and mouse lymphocytes. ONX 0914-treatment impaired primary T cell activation in vitro and in vivo. IP inhibition reduced ERK-phosphorylation sustainment, while leaving NF-κB and other signaling pathways unaffected. Naïve T and B cells expressed nearly exclusively immuno- or mixed proteasomes but no standard proteasomes and IP inhibition but not IP-deficiency induced mild proteostasis stress, reduced DUSP5 expression and enhanced DUSP6 protein levels due to impaired degradation. We show that broad-spectrum proteasome inhibition and immunoproteasome inhibition have distinct effects on T cell activation at the molecular level. Notably, ONX 0914-treated T cells recovered from proteostasis stress without apoptosis induction, apparently via Nrf1-mediated up-regulation of standard proteasomes. In contrast, B cells were more susceptible to apoptosis after ONX 0914-treatment. Our data thus mechanistic insights how IP inhibition functionally impedes T and B cells likely accounting for its therapeutic benefits.